2022
DOI: 10.1002/advs.202203111
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Electrophilic‐Attack Doping Mechanism for Efficient and Universal p‐Doping of Organic Semiconductors

Abstract: Doping is of great importance to tailor the electrical properties of semiconductors. However, the present doping methodologies for organic semiconductors (OSCs) are either inefficient or can only apply to some OSCs conditionally, seriously limiting their general applications. Herein, a novel p‐doping mechanism is revealed by investigating the interactions between the dopant trityl tetrakis(pentafluorophenyl) borate (TrTPFB) and poly(3‐hexylthiophene) (P3HT). It is found that electrophilic attack of the trityl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…P3HT exhibited a conductivity of 6.6 (±0.5) Â 10 À5 S cm À1 at 0.2 mol% F4TCNQ concentration, and dramatically reached its maximum conductivity of 1.9 (±0.2) Â 10 À2 S cm À1 at an F4TCNQ concentration of 2.5 mol%. This value is very comparable to the previous reports on the doped P3HT, for instance the one by Kim et al [23] and the other by Hu et al [26], though, it is lower than that of the state-of-the-art doped P3HT due primarily to the lower Mn in the current study. It was shown that increasing the Mn by ca.…”
Section: Electrical Measurements and Doping Characterizationssupporting
confidence: 91%
“…P3HT exhibited a conductivity of 6.6 (±0.5) Â 10 À5 S cm À1 at 0.2 mol% F4TCNQ concentration, and dramatically reached its maximum conductivity of 1.9 (±0.2) Â 10 À2 S cm À1 at an F4TCNQ concentration of 2.5 mol%. This value is very comparable to the previous reports on the doped P3HT, for instance the one by Kim et al [23] and the other by Hu et al [26], though, it is lower than that of the state-of-the-art doped P3HT due primarily to the lower Mn in the current study. It was shown that increasing the Mn by ca.…”
Section: Electrical Measurements and Doping Characterizationssupporting
confidence: 91%
“…Such efficiencies were slightly lower than that of F 4 TCNQ (ca. 35% at a 10% doping ratio), which was attributed to the bulkiness of the PBLG arms that could inhibit the electron transfer between P3HT segments or chains , (Figure a, purple arrow). This also explained why the polaron generation efficiency decreased with increased doping ratios: the steric hindrance from the PBLG arms would apparently increase as the grafting density increased.…”
Section: Resultsmentioning
confidence: 99%
“…As a proof of concept, we went on to assess these polypeptides’ capability of peptidylation and doping of OSCs. Many of these OSCs are known to be doped by Lewis acids, and very recently, we have reported a highly effective doping method by using a carbenium salt, trityl tetra­(pentafluorophenyl)­borate (TrTPFB) . The trityl cation reacts with various semiconductive polymers by performing electrophilic attacks on the aromatic moieties on the polymers, yielding the corresponding Wheland intermediates that subsequently disproportionate to generate polarons for substantially increased conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong electrophilic and electron-deficient nature of tropylium cation acts as a reactive species for doping organic semiconductors. [50] Upon heating, tropylium cations can dissociate from T-PCCp ion pair into a free or weakly ionic bonded cation. This electrophilic cation can attack electron-rich 3,4-ethylenedioxythiophene (EDOT) on the P1 polymer backbone.…”
Section: Doping Mechanisms Discussionmentioning
confidence: 99%